2002
DOI: 10.1191/0269215502cr524oa
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with cardiac rehabilitation attendance: a systematic review of the literature

Abstract: A number of factors predict cardiac rehabilitation attendance and some of these are potentially modifiable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
183
3
7

Year Published

2003
2003
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 218 publications
(205 citation statements)
references
References 44 publications
(127 reference statements)
12
183
3
7
Order By: Relevance
“…Non-participant research suggests that non-attenders may be missing out (Hildingh and Fridlund, 2001;Cooper et al, 2002). This study found that for many interviewees non-use represented a 'missed opportunity' to aid rehabilitation, assist secondary prevention, and support families.…”
Section: Discussionmentioning
confidence: 85%
“…Non-participant research suggests that non-attenders may be missing out (Hildingh and Fridlund, 2001;Cooper et al, 2002). This study found that for many interviewees non-use represented a 'missed opportunity' to aid rehabilitation, assist secondary prevention, and support families.…”
Section: Discussionmentioning
confidence: 85%
“…While comprehensive reviews of patient-level factors affecting CR enrollment can be found in the literature [13,14,40,41], this research shows that we can no longer focus solely on the patient level without examining the broader issues affecting CR at the physician and health system level. Moreover, while there have been calls in the literature to develop means to overcome under-utilization of CR services, few interventions have been developed, tested or implemented, particularly at the physician level [49].…”
Section: Discussionmentioning
confidence: 95%
“…Factors identified in this study were marital status, CR barriers, and distance to CR. Previous research has identified these factors as important in CR utilization [40,41]. Having spousal support for instance has been shown to positively affect CR participation, and involving including spouses in referral discussions, or enlisting the support of adult children where patients do not have a partner [45] could promote greater CR enrollment.…”
Section: Discussionmentioning
confidence: 99%
“…The strength and the content of the physician's recommendation may be an important variable. Eligible patients in the general population who fail to attend cardiac rehabilitation programs are less likely to perceive that their physician recommends cardiac rehabilitation (6,30,31) and are less likely to understand how cardiac rehabilitation can help them (32).…”
Section: Discussionmentioning
confidence: 99%